Method for cultivating hens laying selenium-enriched eggs - Xu Jiechi; Chen Xiaolin (2016)
The invention discloses a method for cultivating hens laying selenium-enriched eggs. High-selenium active feed is fed to hens from a brooding period, the henhouse temperature and appropriate stocking are controlled, the feeding amount of the high-selenium active feed is gradually increased during an egg laying peak period of the hens, and the hens are fed in a mode of combining grazing and feed supplementing in a fence. Compared with the prior art, the content of selenium in eggs produced by the hens fed according to the method is 10-15 times that of selenium in ordinary eggs in the prior art. The selenium-enriched eggs laid by the hens fed according to the feeding method can supplement enough selenium while supplementing protein, and the immunocompetence and reproductive performance of the hens can be improved; and by combination with other nutritional ingredients in the feed, medicines containing the selenium element in the prior art can be replaced. Moreover, the selenium-enriched eggs have no side effect